Faktor-Faktor yang Mempengaruhi Lama Penyembuhan Luka Diabetes Mellitus di Klinik Pratama Hanifah Kota Tangerang 2024 - Tiwi Ade Maharani; Asha Grace Sicilia; Irfan Ilmi; Dalva Gumilar (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The wound healing duration in Diabetes Mellitus (DM) patients is influenced by factors such as age, nutritional status, blood sugar levels, diet adherence, physical activity, and medication compliance. In diabetic foot ulcer cases, healing is often impaired, increasing the risk of amputation if not properly managed. This study investigates factors affecting wound healing duration in DM patients at Hanifah Pratama Clinic, Tangerang City. A quantitative cross-sectional design was used, with a sample of 40 DM patients with diabetic foot ulcers selected through total sampling. Instruments included weight scales and height meters for nutritional status, Easy Touch® GCU for blood glucose levels, the Morisky Medication Adherence Scale (MMAS) for medication compliance, and the Bates-Jensen Wound Assessment Tool (BWAT) for wound assessment. Data analysis utilized the Chi-Square bivariate test and backward logistic regression multivariate test. Results showed that nutritional status significantly influenced wound healing duration (p < 0.05), with an OR of 28.884 (95% CI 2.760-302.240), indicating that patients with good nutritional status are 28.884 times more likely to heal faster. In conclusion, nutritional status is the dominant factor affecting wound healing duration in DM patients at Hanifah Pratama Clinic. This study highlights the importance of improving treatment quality and wound care while encouraging better nutritional interventions in diabetic foot ulcer management.